The Art of the Qur’an in Java - Gallop, Annabel Teh (Lajnah Pentashihan Mushaf Al-Qur'an, 2012)
A study of QurÃ¢â‚¬â„¢an manuscripts from Southeast AsiaÃ‚Â Ã‚Â has revealed a number of distinctive artistic schools.Ã‚Â The common denominator of each school is a strong sense of regional identity, with particular styles of manuscript illumination associated with Aceh, the states of Terengganu, Kelantan and Patani on the East Coast of the Malay peninsula, and the south Sulawesi diaspora communities. Large numbers of illuminated QurÃ¢â‚¬â„¢an manuscripts are also known from Java, but here we find a wide variety of decorative styles, meaning it is not possible to talk of a single Ã¢â‚¬ËœJavaneseÃ¢â‚¬â„¢ school of QurÃ¢â‚¬â„¢anic illumination.Ã‚Â This article lists a few distinctive features associated with Javanese illuminated Qur'an manuscripts, as a contribution towards a better understanding of the art of the Qur'an in Java.